Cross-media communication in context: A mixed-methods approach - Thorhauge, Anne Mette; Lomborg, Stine (MedieKultur: Journal of media and communication research, 2016)
In this article, we suggest and discuss a qualitative, multi-methods approach to data collected on smartphones as a way of uncovering a user-centred perspective on cross-media communication. As an individualised multimedia device, the smartphone represents a relevant starting point for studying individual users’ cross-media practices. Moreover, the technological affordances of the smartphone, including built-in sensors and GPS tracker as well as features for capturing photo, audio and video material, enable the collection of a wide range of data. These properties have mainly been approached from a quantitative point of view focusing on automatically logged use data as an alternative to, for instance, survey data. Complementing this evidence, we argue that a qualitative, multiple-method approach to data collected on smartphones provides crucial insight into the contexts and everyday practices of cross-media communication.